THE INFLUENCE OF SEXUAL HARASMENT ON BUSINESS RESULTS OF COMPANIES IN SERBIA THE LEGAL - BIHEVIORAL ASPECTS - Đurić, Zvezdan; Erić, Ivana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Abstract: Sexual harassment at work is one of the biggest stressors that can cause numerous consequences. It has legal, moral and behavioral dimensions. Because of that, in the paper were presenting the legal definition, certain moral dilemmas and behavioral implications. Surely, viewed from the perspective of business implications, sexual harassment leaves negative psychological and general health consequences, as well as a significant decline in business performance. So, the modern world organizations are trying to eradicate such a big monster. However, in many traditional environments, to which belong and ours this problems have not been considered as significant for many years. During the 2005. year, the Law prohibited sexual harassment that happens in our country, which demonstrated good will to eradicate such ugly practices. An empirical research was conducted with the intention of determining the actual presence of sexual abuse and its implications for the business performance of organizations in Serbia.